The Effect of Photobiomodulation on Temporomandibular Pain and Functions in Patients With Temporomandibular Disorders: An Updated Systematic Review of the Current Randomized Controlled Trials: Photobiomodulation in temporomandibular disorders - Farshidfar, Nima; Farzinnia, Golnoush; Samiraninezhad, Nazafarin; Assar, Sahar; Firoozi, Parsa; Rezazadeh, Fahimeh; Hakimiha, Neda (Journal of Lasers in Medical Sciences, 2023)
Introduction: Temporomandibular disorders (TMDs) are the most prevalent non-dental origin orofacial pain affecting the temporomandibular joints and orofacial muscles. This systematic review was conducted to update evidence about the effects of Photobiomodulation therapy (PBMT) on pain intensity, TMJ movements, electromyography (EMG) activity, pressure pain threshold (PPT), and TMJ sound in patients with TMDs. Methods: A search was conducted in Web of Science, PubMed/Medline, and Scopus databases using from January 2000 to September 2022. Results: A total of 40 studies were included. All included studies except one provided information on pain intensity; 27 studies showed a reduction in pain intensity in PBMT groups compared to control groups. Seven out of 15 studies, which reported maximum mouth opening (MMO), showed a greater MMO in PBMT groups than in placebo groups. In eight out of ten studies, lateral movement (LM) was greater in PBMT groups. Moreover, in three studies out of four, protrusive movement (PM) was reported to be greater in the PBMT group. Four out of nine studies showed a greater PPT in the PBMT group. Reduced TMJ sounds in the PBMT group were reported in two out of five studies. In addition, in most studies, no difference in EMG activity was detected between the two groups. Conclusion: This updated systematic review showed the promising effects of PBMT on the alleviation of pain and improvement in MMO. Using the infrared diode laser with a wavelength ranging between 780-980 nm, an energy density of<100 J/ cm2, and an output power of≤500 mW for at least six sessions of treatment seems to be a promising option for treating mentioned TMDs signs and symptoms based on the previously reported findings.